Cryoballoon ablation for treatment of patients with refractory esophageal neoplasia after first line endoscopic eradication therapy - Alzoubaidi, Durayd; Hussein, Mohamed; Sehgal, Vinay; Makahamadze, Christwishes; Magee, Cormac G.; Everson, Martin; Graham, David; Sweis, Rami; Banks, Matthew; Sami, Sarmed S.; Novelli, Marco; Lovat, Laurence; Haidry, Rehan (Endoscopy International Open, 2020)
Background and study aims Cryoablation with the Cryoballoon device is a novel ablative therapy that uses cycles of freezing and thawing to induce cell death. This single-center prospective study evaluated the feasibility of the focal cryoablation device for the treatment of areas of refractory esophageal neoplasia in patients who had undergone first line endoscopic eradication therapy (EET). Complete remission of dysplasia (CR-D) and complete remission of intestinal metaplasia (CR-IM) at first follow-up endoscopy, durability of disease reversal, rates of stenosis and adverse events were studied.Patients and methods Eighteen cases were treated. At baseline, nine patients had low-grade dysplasia (LGD), six had high-grade dysplasia (HGD) and three had intramucosal carcinoma (IMC). Median length of dysplastic Barrett’s esophagus (BE) treated was 3 cm. The median number of ablations per patient was 11. Each selected area of visible dysplasia received 10 seconds of ablation. One session of cryoablation was performed per patient. Biopsies were performed at around 3 months post-ablation.Results CR-D was achieved in 78 % and CR-IM in 39 % of patients. There were no device malfunction or adverse events. Stenosis was noted in 11 % of cases. At a median follow up of 19-months, CR-D was maintained in 72 % of patients and CR-IM in 33 %.Conclusions Cryoablation appears to be a viable rescue strategy in patients with refractory neoplasia. It is well tolerated and successful in obtaining CR-D and CR-IM in patients with treatment-refractory BE. Further trials of dosimetry, efficacy and safety in treatment-naïve patients are underway.